Legal academics and progressive politics in South Africa: Moving beyond the ivory tower - PULP FICTIONS No.2 - Karin van Marle (Pretoria University Law Press (PULP), 2006)
Legal academics and progressive politics in South Africa: Moving beyond the ivory tower - PULP FICTIONS No.2 Edited by Karin van Marle 2006 ISSN: 1992-5174 Pages:30 Print version: Available Electronic version: Free PDF available